The influence of pneumoperitoneum used in laparoscopic surgery on an intraabdominal tumor growth - Volz, Joachim; Volz-Köster, Stefanie; Paweletz, Neidhard (Cancer, 1999)
BACKGROUND: Numerous clinical reports have raised the possibility that laparoscopic cancer surgery has an inherently detrimental effect on tumor growth. The aim of the current study was to examine the influence of a pneumoperitoneum on the morphology of the peritoneum and the intraperitoneal tumor cell implantation and growth in the case of intraabdominal spread of tumor cells. METHODS: Black mice were stratified into 2 groups of 36 animals each. A CO2 pneumoperitoneum was induced for 30 minutes in Group 1 and 200,000 cells of a malignant melanoma were injected intraperitoneally. In Group 2 only tumor cells were injected. After a defined period of hours, 4 animals were killed and the peritoneum was examined by scanning electron microscopy. RESULTS: In Group 1, starting 2 hours after release of the pneumoperitoneum, strong alterations of the peritoneum became visible and parts of the underlying basal lamina were laid bare. Tumor cells attached to the free basal lamina and formed predominantly diffuse metastases throughout the peritoneum within the next 96 hours. No diffuse changes of the peritoneal surface and no diffuse metastases were observed in the second group. Singular metastases followed gravity and involved the anterior abdominal wall. CONCLUSIONS: Because these findings explain the clinical findings of intraabdominal metastases after laparoscopy the authors conclude that the pneumoperitoneum provokes particular damage to the peritoneum that induces a specific intraperitoneal tumor growth. [See also editorial counterpoint on pages 747-8 and reply to counterpoint on pages 749-50, this issue. Cancer 1999;86:770-4. © 1999 American Cancer Society.
Elektronische Reproduktion der Druckausgabe
Gesehen am 15.04.2021